Thermal sensitivity and niche plasticity of generalist and specialist leaf-endophytic bacteria in Mangrove Kandelia obovata - Rajapakshalage Thashikala Nethmini; Huaxian Zhao; Lianghao Pan; Xinyi Qin; Jiongqing Huang; Qing He; Xiaofang Shi; Gonglingxia Jiang; Qinghua Hou; Qingxiang Chen; Xiaolei Li; Ke Dong; et al. (Communications Biology)
Abstract Leaf endospheres harbor diverse bacterial communities, comprising generalists and specialists, that profoundly affect ecosystem functions. However, the ecological dynamics of generalist and specialist leaf-endophytic bacteria and their responses to climate change remain poorly understood. We investigated the diversity and environmental responses of generalist and specialist bacteria within the leaf endosphere of mangroves across China. Our findings show a predominance of specialists in the mangrove leaf endosphere. Temperature is the key factor driving community dissimilarity in both groups, yet it negatively influences the alpha diversity. Soil nutritional factors, particularly phosphate for generalists and total organic carbon for specialists are critical in shaping the functional profiles. Interestingly, temperature has a limited impact on functional profiles. Stochastic processes govern community assembly in both bacterial groups, altering the β-nearest taxon indices as temperatures increase. Our findings indicate that the halophytic leaf endosphere favors microbial niche specialization, due to its unique microenvironment and discrete niches, showing thermal sensitivity in terms of the microbial community profile. This study provides insights into niche differentiation and environmental adaptation mechanisms of leaf endophytic microbes in woody halophytes in response to environmental perturbations.